Calcium and s100a1 Protein Balance in the brain– Heart axis in Diabetic Male Wistar Rats. - Keneth Iceland, Kasozi; Nakimbugwe, Dorothy; Ninsiima, Herbert Izo; Kasolo, Josephine; Matama, Kevin; Safiriyu, Abass Alao; Owembabazi, Elna; Ssempijja, Fred; Okpanachi, Alfred Omachonu; Valladares, Miriela Betancourt (Kabale University, 2023)
Objectives: Calcium deregulation in diabetes mellitus (DM) is central to the brain–heart axis pathology. This has led to the use of medical plants in complementary medicine such as Amaranthus hypochondriacus (GA). The objective of the study was to establish the effects of grain amaranth feed supplementation on calcium, s100al protein and antioxidant levels on the brain–heart axis in diabetic male Wistar rats. Methods: The study involved six groups (n=5) with DM being induced in 20 rats. To the diabetic rats, Group I received mixtard®, Group II was positive control, Groups III and IV received GA feed supplementation at 25 and 50%. In the nondiabetic rats (n=10), Group V received 50% grain amaranth while Group VI was the negative control. The brain and heart tissues were harvested after five weeks and processed using standard methods. Results: Grain amaranth feed supplementation led to improved calcium levels in DM as compared to the positive control. This also led to increased s100a1, antioxidant levels in the brain–heart axis during DM. This then protected the tissues against oxidative damage, thus preserving tissue function and structure. Conclusions: Grain amaranth’s actions on calcium signaling subsequently affected s100a1 protein levels, leading to improved tissue function in diabetes. Keywords: Calcium, T2DM, Ethnomedicine, Grain Amaranth.